Optimization of Civil Servants' Performance at the Department of Population and Civil Registration, South Papua Provincial Government - Jaftoran, Ferdinandus; Daraba, Dahyar; Madjid, Udaya; Poli, Arnold; Basir, Hestiwati (Jurnal Indonesia Sosial Sains, 2024)
The main problem in our study is the Unorderly Administration of Population and Civil Registration Services at the Population and Civil Registration and Community and Village Empowerment Service of Merauke Regency. This is because South Papua Province is a new province. this research aims to analyze the implementation, obstacles, and efforts in applying Ministerial Regulation No. 6 of 2022 for state civil servants at the service in question. The research method we use a qualitative descriptive approach was used, with a Likert Scale method applied to measure respondent tendencies through questionnaires. Data was collected from 5 leaders, 10 task implementers, and 135 community representatives across 4 sub-districts. Primary data came from interviews and questionnaires, while secondary data was obtained from documents. The results show that key dimensions, including resource availability, facilities, performance, SOP clarity, and effectiveness, did not meet performance standards, with scores ranging from 33-66%. However, dimensions such as knowledge, budget, skills, and innovation were within acceptable standards. Based on these findings, the study recommends transitioning from manual to digital services to improve efficiency and reduce costs. Further research and collaboration between government and universities are also recommended to support community service efforts.